The mechanical and heat conducting properties of dental composites - Kamalak, Hakan; Oz, Erdinc; Demirel, Serkan; Altin, Serdar (Biointerface Research Applied Chemistry, 2016)
In this study, it was studied the microstructural, mechanical and heat conducting properties of Ca added and un-added commercial light-cure restorative composite resins, in detail. The main goal of the study is the investigation of the mechanical strength and the thermal conductivity of the samples by Ca addition which the Ca ions have biocompatible properties. We used 0 %, 3 %, 6 % and 9 % Ca addition in the commercial light-cure restorative composite resin named Cavex Nano, Amaris, Tetrik N Flow, Solitare. The structural properties were analyzed by using XRD, FTIR, SEM, and optical microscope. The mechanical and heat conducting properties of the samples were investigated by micro hardness and thermal conductivity measurement system, respectively. It is found that there are two main structures in the materials; one is the organic content and the other is the crystalline content. We found that the Ca addition causes diffusion in the main matrix or accumulated in the inergranular region of the composite resins depending on the commercial materials. The thermal and mechanical properties showed a strong relation between the composite resin and Ca content. It is concluded that the diffusion of Ca into the main matrix causes an improvement of both the mechanical and thermal conducting properties which can be used in commercial composite resins in the near future.
Keywords: thermal conductivity; biomaterials; mechanical strength